Attitudes towards the resuscitation of periviable infants: a national survey of American Muslim physicians. (15th October 2015) - Arzuaga, Bonnie; Adam, Huda; Ahmad, Maha; Padela, Aasim
Abstract: Aim: To examine the associations between American Muslim physicians' characteristics and intended behaviours towards resuscitation of 22‐ and 23‐week gestation infants. Methods: This national survey of physician members of the Islamic Medical Association of North America inquired about physician religiosity, their practice of referring to Islamic resources for bioethical guidance, their preferred model of patient–doctor decision‐making and the perceived importance of quality‐of‐life determinations with respect to medical decision‐making. Four vignettes described birth of a 22‐ and a 23‐week gestation infant. Respondents were given estimated survival data for each and asked whether they would attempt resuscitation. Results: A total of 255 of 626 responses received. About 51% and 85% of respondents believed that a 22‐ and a 23‐week gestation infant should be resuscitated, respectively. If parents opposed resuscitation, 44% (22 weeks) and 46% (23 weeks) of respondents still endorsed resuscitating. Respondents who were more religious, referred more often to Islamic bioethical resources and did not believe that quality‐of‐life determinations were tied to life's value had greater odds of endorsing resuscitation in many of the scenarios. Conclusion: American Muslim physicians have high rates of support for delivery room resuscitation of periviable infants. Their intended behaviour appears to associate with religious values. Abstract :